Bionic Design and Performance of Electrode for Bioelectrical Signal Monitoring (Adv. Mater. Interfaces 25/2022). Issue 25 (2nd September 2022) - Yuan, Cong; Ji, Keju; Zhang, Qian; Yuan, Peng; Xu, Yilin; Liu, Jing; Huo, Tingwei; Zhao, Jiahui; Chen, Jian; Song, Yi; Long, Yi; Dai, Zhendong
Abstract : Biomimetic Microneedles‐Based Adhesive Electrode In article number 2200532, Cong Yuan, Keju Ji, Zhendong Dai, and co‐workers develop a bionic electrode for bioelectrical signal monitoring, which utilizes the mechanical locking of the microneedle array and the adhesion to synergistically enhance the stable adhesion on the skin surface, and realizes continuous and robust bioelectric monitoring.